Clinical Presentation and Outcomes of Severe Acute Respiratory Syndrome Coronavirus 2–Related Encephalitis: The ENCOVID Multicenter Study. (28th September 2020) - Pilotto, Andrea; Masciocchi, Stefano; Volonghi, Irene; Crabbio, Massimo; Magni, Eugenio; De Giuli, Valeria; Caprioli, Francesca; Rifino, Nicola; Sessa, Maria; Gennuso, Michele; Cotelli, Maria Sofia; Turla, Marinella; et al.
Abstract: Background: Several preclinical and clinical investigations have argued for nervous system involvement in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Some sparse case reports have described various forms of encephalitis in coronavirus disease 2019 (COVID-19) disease, but very few data have focused on clinical presentations, clinical course, response to treatment, and outcomes. Methods: The SARS-CoV-2 related encephalopaties (ENCOVID) multicenter study included patients with encephalitis with full infectious screening, cerebrospinal fluid (CSF), electroencephalography (EEG), and magnetic resonance imaging (MRI) data and confirmed SARS-CoV-2 infection recruited from 13 centers in northern Italy. Clinical presentation and laboratory markers, severity of COVID-19 disease, response to treatment, and outcomes were recorded. Results: Twenty-five cases of encephalitis positive for SARS-CoV-2 infection were included. CSF showed hyperproteinorrachia and/or pleocytosis in 68% of cases whereas SARS-CoV-2 RNA by reverse-transcription polymerase chain reaction resulted negative. Based on MRI, cases were classified as acute demyelinating encephalomyelitis (ADEM; n = 3), limbic encephalitis (LE; n = 2), encephalitis with normal imaging (n = 13), and encephalitis with MRI alterations (n = 7). ADEM and LE cases showed a delayed onset compared to the other encephalitis cases ( P  = .001) and were associated with previous, more severe COVID-19 respiratory involvement. Patients with MRI alterations exhibited worse response to treatment and final outcomes compared to those with other encephalitis. Conclusions: SARS-CoV-2 infection is associated with a wide spectrum of encephalitis characterized by different clinical presentation, response to treatment, and outcomes. Abstract : In this prospective multicenter study including 25 cases of encephalitis in severe acute respiratory syndrome coronavirus 2 infection, the majority of patients presented clinical, imaging, and cerebrospinal fluid findings, arguing for a cytokine-mediated mechanism.